Euroscience-Informed Instructional Design Exploring The Impact Of Cognitive Load Management On Stem Learning Outcomes - Supratpi; Arintoko, Lasarus; Oenjoyo, Paulus (Education : Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study explores the integration of neuroscience-informed instructional design in STEM education, emphasizing the role of cognitive load management in enhancing learning outcomes. Using a quasi-experimental pretest–posttest control group design, the research involved 60 high school students divided into experimental and control groups. The instructional design for the experimental group was developed based on Cognitive Load Theory and neuroscience principles such as chunking, dual coding, and attention-focused scaffolding. Data were collected through standardized tests, EEG headbands, and attention trackers to measure both cognitive performance and neurobiological responses. Results showed that students in the experimental group achieved significantly higher posttest scores, with an average improvement of 25 points compared to the control group (p < 0.05; large effect size). EEG data further indicated that the experimental group demonstrated higher and more consistent levels of cognitive focus throughout the learning sessions. These findings highlight the importance of aligning instructional strategies with brain-based principles to optimize STEM learning, particularly in cognitively demanding contexts. The study contributes a practical framework for neuroscience-informed pedagogy and provides empirical evidence of its effectiveness in reducing cognitive overload while improving student engagement.